Major pathways involved in macrophage polarization in cancer - Kerneur, Clément; Cano, Carla E.; Olive, Daniel (Frontiers in Immunology, 2022)
Macrophages play an important role in tissue homeostasis, tissue remodeling, immune response, and progression of cancer. Consequently, macrophages exhibit significant plasticity and change their transcriptional profile and function in response to environmental, tissue, and inflammatory stimuli resulting in pro- and anti-tumor effects. Furthermore, the categorization of tissue macrophages in inflammatory situations remains difficult; however, there is an agreement that macrophages are predominantly polarized into two different subtypes with pro- and anti-inflammatory properties, the so called M1-like and M2-like macrophages, respectively. These two macrophage classes can be considered as the extreme borders of a continuum of many intermediate subsets. In one hand, M1 macrophages are pro-inflammatory cells that initiate an immunological response, damage tissue integrity, and decrease tumorigenicity overall, by fostering robust T and NK cell anti-tumoral responses. On the other hand, M2 macrophages are anti-inflammatory phagocytes involved in tissue remodeling and tumor growth, that promote cancer cell proliferation, invasion, tumor metastasis, angiogenesis and participate to immune suppression. These decisive roles in tumor progression occur through the secretion of cytokines, chemokines, growth factors, and matrix metalloproteases, as well as by the expression of immune checkpoint receptors in the case of M2 macrophages. Moreover, macrophage plasticity is supported by stimuli from the Tumor Microenvironment (TME) that are relayed to the nucleus through membrane receptors and signaling pathways that result in gene expression reprogramming in macrophages, thus giving rise to different macrophage polarization outcomes. In this review, we will focus on the main signaling pathways involved in macrophage polarization that are activated upon stimulation, ligand-receptor recognition, and in the presence of other immunomodulatory molecules in cancer context.